Features of integrated ultrasound research of the orbit in the evaluation of the forecast results of prosthetics in subatrophy and microphthalmia - E. N. Verigo; R. A. Gundorova; T. N. Kiseleva; M. I. Shtilman; K. A. Ramazanova; I. A. Pryahina; A. A. Artyuhov; G. V. Kruzhkova; E. P. Cadovskaya; N. V. Lavrentjeva (Oftalʹmologiâ)
A comprehensive echographic study of the orbit using an immersion environment, including high-gray-scale scanning, echo densitometry, volumetric ultrasound scan and color Doppler mapping in 19 patients with post-traumatic subatrophy and 7 patients with congenital microphthalmia. Found that low rates of eye prosthesis in anophthalmia in the late periods is due to insufficient volume of the musculoskeletal stump; if in the orbit exist a reduced in size eye (anteroposterior axis of 10.0 mm or more), the using of prosthesis does not develop deformation of the facial skeleton; the visualization of bloodstream in the great vessels at 2nd — 3rd stages ofsubatrophy and microphthalmia testifies the preservation of blood supply of the structures of the eye and orbit, presence of trophic.